Investigation of Economic, Scientific, and Social Values of Wildlife to Human Societies - Olfat, Ghulamhaidar (Journal of Natural Sciences – Kabul University, 2022)
The study of wild animals is interesting and valuable in several ways. It is crucial to understand the value and importance that wild animals hold. Wildlife is an important natural resource that can be utilized by humans in various ways, including ethical, cultural, commercial, recreational, and environmental aspects. Wildlife is closely connected to society, tradition, education, culture, economy, recreation, and ecology. These creatures have contributed to making our planet a place of joy, happiness, peace, and prosperity. However, wild animals not only have positive importance but also pose negative impacts, such as damage to agriculture, serving as disease reservoirs, and conflicts with humans.